Penerapan Teknologi Internet of Things (IoT) untuk Monitoring Kualitas Udara dalam Ruangan - Aswaldi, Haikal (Lembaga Publikasi Ilmiah Nusantara, 2025)
Indoor air quality plays a crucial role in the health and comfort of occupants, especially in enclosed environments such as homes, offices, and public spaces. Decreased air quality can lead to various health problems, including allergies, respiratory problems, and decreased work productivity. With the advancement of technology, the Internet of Things (IoT) has become an innovative solution for real-time air quality monitoring. This research aims to design and implement an IoT-based air quality monitoring system capable of detecting environmental parameters such as temperature, humidity, carbon dioxide (CO₂) concentration, and dust particles (PM2.5). This system consists of environmental sensors integrated with a microcontroller and connected to a cloud platform for online data storage and visualization. Test results show that the system can provide accurate data and is responsive to changes in air conditions. The system is also equipped with an automatic notification feature that alerts users when air quality decreases below normal thresholds. With this approach, users can take early preventative measures against health risks caused by exposure to polluted air. This research shows that the application of IoT in air quality monitoring is very effective and can be applied on a household and commercial scale.